BASEL III: Long-term impact on economic performance and fluctuations - Paolo Angelini; Laurent Clerc; Vasco Cúrdia; Leonardo Gambacorta; Andrea Gerali; Alberto Locarno; Roberto Motto; Werner Roeger; Skander Van den Heuvel; Jan Vlécek (Federal Reserve Bank of New York, 2011)
We assess the long-term economic impact of the new regulatory standards (the Basel III reform), answering the following questions: 1) What is the impact of the reform on longterm economic performance? 2) What is the impact of the reform on economic fluctuations? 3) What is the impact of the adoption of countercyclical capital buffers on economic fluctuations? The main results are the following: 1) Each percentage point increase in the capital ratio causes a median 0.09 percent decline in the level of steadystate output, relative to the baseline. The impact of the new liquidity regulation is of a similar order of magnitude, at 0.08 percent. This paper does not estimate the benefits of the new regulation in terms of reduced frequency and severity of financial crisis, analyzed in Basel Committee on Banking Supervision (2010b). 2) The reform should dampen output volatility; the magnitude of the effect is heterogeneous across models; the median effect is modest. 3) The adoption of countercyclical capital buffers could have a more sizable dampening effect on output volatility. These conclusions are fully consistent with those of reports by the Long-term Economic Impact Group (Basel Committee on Banking Supervision 2010b) and the Macroeconomic Assessment Group (2010b).
Keywords: E44; E61; G21; 330; Basel III; countercyclical capital buffers; financial (in)stability; procyclicality; macroprudential